Learning Media to Improve Numeracy Skills and Motivation of Students - Al-Qoyyim, Thufail Mujaddid; Nabila, Siti Maulidiya; Affan, Affan; Suri, Aida Atika; Muhaini, Muhaini; Hajariah, Siti (Balai Publikasi Indonesia, 2024)
Numeracy ability is a basic ability that students must have to face the progress of the times. This ability guides students to analyze and solve mathematical problems and problems in everyday life. Even though it is very important, the numeracy skills of students in Indonesia are still very low. Therefore, efforts need to be made to improve and adjust strategies in the learning process so that students' numeracy abilities can increase. One effort is to use learning media. This research aims to find out what learning media are used by teachers to improve the numeracy skills of elementary school students, especially at the Tahfidzul Quran An-Nahl Mataram Integrated Islamic Elementary School. This research method is through teacher interviews and learning observations for 5 months in the odd semester of the 2023/2024 academic year. There are several media used by teachers in the process of improving numeracy skills at the Tahfidzul Quran An-Nahl Mataram Integrated Islamic Elementary School, including the addition and subtraction board, an introduction to measuring instruments board, rupiah specimen currency media, and a long unit ladder prop. All media used by teachers can increase student activity and involvement, learning outcomes, and student learning motivation.